THE PROSPECT OF BUSINESS DEVELOPMENT ON EEL FISH(Anguilla sp) CULTIVATIONIN BALAI LAYANAN USAHA PERIKANAN PRODUKSI BUDIDAYA (BLUPPB) KARAWANG WEST JAVA PROVINCE - Maharie, Trio Nugraha; Zulkarnaini, Zulkarnaini; Warningsih, Trisla (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACK The research was counducted in May 2017 at the in Balai layanan Usaha Produksi Perikanan Budidaya of Karawang West Java Province. This study aims to determine the amount of total investment cost of production, net income, marketing flow, business feasibility analysis, and business development prospects of the business of raising fish in ell Fertilizer Production Business Processing Aquaculture Karawang West Java Province. The method used in this research is survey method.Cultivition of Fresh Fish Cultivation in Balai layanan Usaha Produksi Perikanan Budidaya ofKarawang West Java Province has InvestmentRp. 247.465.000, consisting of fixed capital ofRp. 74.545.000, and working capital of Rp. 172.920.000. Marketing of eel fish atBalai layanan Usaha Produksi Perikanan Budidaya of Karawang West Java Province of crop sold to collector, collector to local consumer, Business Servise Center of Production Fishery of Karawang Cultivatisibility directly to local consumer, and collector directly to overseas consumer. The results of feasibility analysis obtained a profit of Rp. 339.915.000 per cycle (year) and RCR 2,89, FFR 137,35%, dan PPC 0,72years. The prospect of the development of eel farming business in the field of business of fishery aquaculture production business is good enough, based on the criteria of investment, marketing, and fulfillment of all sub-systems of agribusiness (subsystem input supplay, subsystem farming, and subsystem marketing).Keywords: Prospects, Business cultivation of enlargement eel fish, DistrictKarawang